Strategic, Technological, and Innovative Drivers of Women's Digital Awareness in MSMEs: Pendorong Strategis, Teknologi, dan Inovatif Kesadaran Digital Perempuan di UMKM - Salsabila, Nazwa Azahra; Rizky, Muhammad Chaerul; Astuti, Widya Tri; Sitorus, Jevania Marthasya; Purba, Sri Dewi Cristina Putri (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid growth of digital technology within the Industry 4.0 era has transformed economic sectors, including Micro, Small, and Medium Enterprises (MSMEs). Specific Background: In rural settings like Banyumas Village, Langkat Regency, women play a crucial role in MSME development, yet their technological awareness remains understudied. Knowledge Gap: Limited empirical evidence exists on how strategic MSME development and technological innovation affect women's awareness at the village level. Aims: This study investigates the influence of MSME development strategies and Industry 4.0-based innovation and technology on women’s awareness levels. Results: Using a quantitative approach with 60 female MSME actors and multiple linear regression analysis, the study reveals that all three independent variables—MSME development strategies (t = 14.148), innovation (t = 6.378), and technology (t = 4.567)—significantly impact women's awareness (F = 2081.339; sig. = 0.000). The dominant factor is MSME development strategies. An R² value of 0.901 indicates that 90.1% of awareness variation is explained by the model. Novelty: This study offers a rare integrated assessment of strategic and technological factors on women’s awareness within rural MSMEs.Implications: Findings underscore the importance of targeted digital training and mentoring to enhance women's roles in driving technology-based village economies. Highlights: Highlights the impact of digital strategies on women’s awareness in rural MSMEs. Identifies MSME development strategies as the most influential factor. Recommends digital training to boost women’s role in tech-driven economies. Keywords: MSMEs, Innovation, Technology, Industry 4.0, Women Empowerment.